A idéia de história em Walter Benjamin: o passado, a forma e a tradução - Augusto Bruno de Carvalho Dias Leite (2013)
The dissertation deals with the knowledge in general and focus on the analysis of a specific knowledge, the historical. To do so, the dissertation unfolds the work of Jewish-German thinker Walter Benjamin. The historical knowledge, from the design of Benjamins theory of history, is presented as knowledge through the prism of the authors theories of Ianguage and knowledge: theories that subvert the key concept of truth, deconstructed by a consciousness of the natural discontinuity of time. The historian as a translator, Starting from the Benjaminian theory of translation, lastly, is handled by a particular analysis, to fill the apparent vacuum generated by the Benjamin's method of historical presentation.